Internal quality control indicators of cervical cytopathology exams performed in laboratories monitored by the External Quality Control Laboratory - Cinara Zago Silveira Ázara; Edna Joana Cláudio Manrique; Suelene Brito do Nascimento Tavares; Nadja Lindany Alves de Souza; Rita Goreti Amaral (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2014)
PURPOSE: To evaluate the impact of continued education provided by an external quality control laboratory on the indicators of internal quality control of cytopathology exams.METHODS: The internal quality assurance indicators for cytopathology exams from 12 laboratories monitored by the External Quality Control Laboratory were evaluated. Overall, 185,194 exams were included, 98,133 of which referred to the period preceding implementation of a continued education program, while 87,061 referred to the period following this intervention. Data were obtained from the Cervical Cancer Database of the Brazilian National Health Service.RESULTS: Following implementation of the continued education program, the positivity index (PI) remained within recommended limits in four laboratories. In another four laboratories, the PI progressed from below the limits to within the recommended standards. In one laboratory, the PI remained low, in two laboratories, it remained very low, and in one, it increased from very low to low. The percentage of exams compatible with a high-grade squamous intraepithelial lesion (HSIL) remained within the recommended limits in five laboratories, while in three laboratories it progressed from below the recommended levels to >0.4% of the total number of satisfactory exams, and in four laboratories it remained below the standard limit. Both the percentage of atypical squamous cells of undetermined significance (ASC-US) in relation to abnormal exams, and the ratio between ASC-US and intraepithelial lesions remained within recommended levels in all the laboratories investigated.CONCLUSION: An improvement was found in the indicators represented by the positivity index and the percentage of exams compatible with a high-grade squamous intraepithelial lesion, showing that the role played by the external quality control laboratory in providing continued education contributed towards improving laboratory staff skills in detecting cervical cancer precursor lesions.